2016
DOI: 10.1590/s1414-40772016000200013
|View full text |Cite
|
Sign up to set email alerts
|

Cotas e desempenho acadêmico na UFBA: um estudo a partir dos coeficientes de rendimento

Abstract: Resumo: Um debate recorrente em torno das cotas na universidade é a possibilidade do cotista obter rendimento satisfatório a despeito das diferenças no seu processo de formação anterior ao ingresso na Universidade. O objetivo deste estudo é comparar o desempenho de alunos cotistas e não cotistas da Universidade Federal da Bahia (UFBA), reunindo evidências que possam embasar ações institucionais no sentido de assegurar sólida formação a todos os seus alunos. A amostra foi por composta por todos os alunos ativos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
49

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 5 publications
(5 reference statements)
1
15
0
49
Order By: Relevance
“…The first analysis of averages was made for each of the 15 courses taken by students in the first year. The data in table 1 show that in none of the disciplines analyzed, a statistically significant difference was found, however, when analyzing the dirty average, it is clear that students not included in Inclusp have higher performance 11 out of 15 courses, presenting similar results with those found by Bezerra and Gurgel (2012), Peixoto et al (2013) and Mendes Junior (2014). We also observed that in the mathematical courses -Differential and Integral Calculus I, Financial Mathematics, Introduction to Probability and Statistics II and Differential and Integral Calculus II -nonsubsidized students have superior results.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The first analysis of averages was made for each of the 15 courses taken by students in the first year. The data in table 1 show that in none of the disciplines analyzed, a statistically significant difference was found, however, when analyzing the dirty average, it is clear that students not included in Inclusp have higher performance 11 out of 15 courses, presenting similar results with those found by Bezerra and Gurgel (2012), Peixoto et al (2013) and Mendes Junior (2014). We also observed that in the mathematical courses -Differential and Integral Calculus I, Financial Mathematics, Introduction to Probability and Statistics II and Differential and Integral Calculus II -nonsubsidized students have superior results.…”
Section: Resultssupporting
confidence: 67%
“…The shareholder performance is lower, however, there are no statistically significant differences; Quotaholders have less evasion. Peixoto et al(2013) 2012 A ll the university students UFBA…”
Section: Uerjmentioning
confidence: 99%
See 1 more Smart Citation
“…Para verificar se realmente existe a queda da qualidade do ensino, a partir da adoção destas ações afirmativas, estudos que envolvem o rendimentoacadêmico dos alunos beneficiados têm sido desenvolvidos, principalmente em universidades federais e estaduais (Cardoso, 2008;Matos, Ferreira, Pinheiro & Dalmas 2010;Nabeshima, Machado, Martins, Coto & Dias,2011;Dallabona, 2011;Bezerra & Gurgel, 2012;Waltenberg & Carvalho, 2012;Matos, Pimenta, Almeida & Oliveira, 2012;Peixoto, Ribeiro, Bastos & Ramalho, 2013;Piotto & Nogueira, 2013;Golgher, Amaral& Neves, 2014;Mendes Jr, 2014;Carvalho & Cerqueira, 2015).…”
Section: Introductionunclassified
“…Disciplinas ordenadas pelo primeiro eixo de uma análise de coordenadas principais a partir da proporção de respostas a cinco questões que avaliaram características da docência Disciplinas ordenadas pelos dois primeiros eixos de uma análise de coordenadas principais a partir da proporção de respostas a cinco questões que avaliaram características da docência diferença entre as médias de alunos que cursam graduações nas áreas humanas e tecnológicas(PEIXOTO et al, 2016). Isso reflete inclusive no número de diplomados pelo número de vagas oferecidas.…”
unclassified